Reagents and swab tests during the COVID-19 Pandemic: An optimized supply chain management with UAVs - Gabriella Colajanni; Patrizia Daniele; Daniele Sciacca (Operations Research Perspectives, 2022)
In this paper, we develop a supply chain optimization model for the preparation, provision, transportation, and execution of swab tests during COVID-19 pandemic. The proposed approach is based on a multi-tiered network consisting of manufacturing companies of reagents, processing laboratories (where the swab kits are prepared and some swab tests are analyzed), landing stations for UAVs and test centers. As innovations in the supply chain, the sharing of reagents between processing laboratories and the use of UAVs, using 5G technology, are contemplated in the management of the COVID-19 Pandemic. To obtain the optimal solutions of the underlying optimization problem, we provide a variational formulation problem for which results of existence and uniqueness will be provided. Finally, some numerical simulations are examined to validate the effectiveness of our approach.
Keywords: 650; COVID-19 pandemic; Swab tests supply chain optimization; UAVs and 5G technology; Variational inequality theory